Strategy of Pancasila Values in National and State Life - Khairani, Nabilla (International Journal of Students Education, 2025)
The dynamics in actualizing the values of Pancasila in the life of society, nation, and state is a must so that Pancasila remains relevant as a guideline in decision-making and problem-solving in society. Pancasila is neither communism nor capitalism, nor individualism nor collectivism, and neither theocracy nor secular. This position makes the application of Pancasila values in practical life complicated. The dynamics of the actualization of Pancasila can be likened to a pendulum that moves in balance between two extremes. Citizens' loyalty to Pancasila needs to be maintained, while apathy and resistance to it must be minimized. The substance of this dynamic lies in the continuous change and renewal in transforming the values of Pancasila into norms and practices of life, while maintaining its consistency, relevance, and context. Continuous change and renewal occur through internal dynamics (self-renewal) and the absorption of foreign values that are relevant to the development of the Pancasila ideology. The result of all these efforts is the maintenance of the acceptability and credibility of Pancasila among Indonesian citizens and society.